Factors Influencing Utilization of Safe Abortion Services - Aryal, Arjun; Thapa, Pramij; Shrestha, Ava; Acharya, Krishna Prasad (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Objectives: This study aims to identify the factors influencing the utilization of safe abortion services in six districts of Nepal by assessing the perspectives of clients and providers. Methods and Materials: Mixed-methods research was conducted in six districts of Nepal. The study involved interviews with 32 exit clients, using a semi-structured interview schedule combined with in-depth interview guidelines. Quantitative data was analyzed using SPSS 16.0, while qualitative data was analyzed manually through thematic, narrative, and content analysis. Informed consent was obtained from all participants. Results: Most clients had low educational status and a poor economy. Significant reasons for seeking abortion services were willing to have no more children (68.8%), unwanted pregnancy (12.5%), and less birth spacing (9.4%). The primary sources of information on safe abortion services were friends/villagers (53%) and Radio (43.75%). Qualitative inquiry revealed that the sex partners of the clients, community based workers associated with service centers, and former clients of safe abortion services influenced the new clients’ decision to undergo an abortion. Nearly two-thirds (62.5%) of the clients visited the service delivery points without partners/careers. Opening times of the clinics were convenient for 75% of the clients, while the remaining 25% suggested that the clinics should also open for holidays/weekends. Of the clients, 12.5% left the clinic without taking any post-abortion contraceptives. Qualitative inquiry extrapolated that the influence and behaviour of health professionals, cost, time, legal concerns, quality of care, social attitude towards abortion, distance and dependency, and self-efficacy were also crucial factors associated with the utilization of safe abortion services. Conclusion: The study highlights the need for increased awareness, improved access to quality services, and enhanced support systems to ensure that women can make informed decisions about their reproductive health. These findings have implications for policymakers and healthcare providers in developing strategies to address the challenges faced by women seeking safe abortion services.